Trichoglossum benghalense (Geoglossales, Ascomycota) from India: new to science - Chakraborty, Nilanjan; Tarafder, Entaj; Paul, Anamika; Paloi, Soumitra; Acharya, Krishnendu (Phytotaxa, 2022)
The genus Trichoglossum belongs to the family Geoglossaceae (Geoglossomycetes) and they are traditionally known as earth tongues. The genus is characterized by black or dark brown club-shaped apothecia, inoperculate asci, with prominent hymenial setae, septate paraphyses, and long septate ascospores. Currently, this genus includes more than 20 species all over the world. The present novel species (Trichoglossum benghalense) was recorded from the lower Gangetic plain of India, which indicates its cosmopolitan distribution range. A detailed morphological description supported by a DNA sequence phylogram based on Maximum likelihood (ML) and Bayesian posterior probabilities (BPP) analysis, photo-illustrations, and line drawings are provided for this interesting species. A comparison with allied accepted species is also summarized.